Long-term climate-associated dynamics of a tropical seagrass meadow: implications for the future - Richard Unsworth (Marine Ecology Progress Series, 2011)
The long-term changes of tropical intertidal seagrass, mainly Halodule uninervis and Halophila ovalis meadows and their relationship to climate are poorly documented. Developing a greater understanding of the effects of climate on seagrass meadows is critical for estimating the effects of future climate change scenarios. Here we document the temporal dynamics of coastal intertidal seagrass in tropical northeast Australia over 16 yr of detailed monitoring. This study is the first to directly relate such change to long-term climate variability in the Indo-Pacific region and southern hemisphere. Regression modelling was used to relate seagrass biomass and meadow area measurements to climate data. The aboveground biomass and area of the meadow were correlated with the interacting factors of air temperature, precipitation, daytime tidal exposure and freshwater runoff from nearby rivers. Elevated temperature and reduced flow from rivers were significantly correlated (R2 = 0.6, p < 0.001) with periods of lower seagrass biomass. Results of this study have important implications for the long-term viability of seagrasses with regard to climate change scenarios. Modelling of our findings indicates that future higher temperatures could be detrimental to Indo-Pacific intertidal, coastal and estuarine seagrass meadows.